Design and fabrication of compression test rig for fibre-reinforced polymer composites. (8th December 2014) - Muhammad, N.; Jumahat, A.; Hamzah, M. H.; Mahmud, J.
<x content-type="archive" xml:space="preserve">Abstract</x> Compressive strength is one of the most important considerations when designing fibre-reinforced polymer (FRP) composite structures. This property is obtained from the stress-strain response of FRP specimen loaded in compression. Compression tests using shear-loading or end-loading methods usually cause premature failure of the specimens or failure near to/in tabs. Therefore, the purpose of this study is to design a test rig for compression testing that combines both shear- and end-loading methods. Computer-Aided Three-Dimensional Interactive Application software was used to design parts and the whole system of the test rig, namely UiTM dual guide compression test fixture. The performance of the test rig was evaluated by conducting compression tests on woven carbon, glass and Kevlar fibre-reinforced polymer composites samples. It was observed that all specimens failed within the specimen gauge length, implying that the tests were successful.